Therapeutic approach for type 1 diabetes mellitus using the novel immunomodulator FTY720 (fingolimod) in combination with once‐daily injection of insulin glargine in non‐obese diabetic mice - Tsuji, Takumi (Blackwell Publishing Ltd, 2011)
Aims/Introduction:  The therapeutic effectiveness against type 1 diabetes mellitus (DM) of the novel immunomodulator FTY720 (fingolimod), alone and in combination with insulin glargine, was examined in the non‐obese diabetic (NOD) mouse model. Materials and Methods:  Female NOD mice that had developed DM spontaneously were divided into four groups: (i) an FTY720 (0.1 mg/kg, p.o., twice weekly)‐treated group; (ii) an insulin glargine (1.0 IU, s.c., once daily)‐treated group; (iii) a combination FTY720 + insulin glargine (0.1–1.0 IU, s.c., once daily)‐treated group; and (iv) a placebo (vehicle)‐treated group. Treatment was initiated at the time of onset of DM and continued for 70 days or until death. The therapeutic efficacy of FTY720, insulin glargine and FTY720 + insulin glargine was evaluated by measuring the ratio of insulin‐positive β‐cells/total islet area, the extent of islet inflammation (insulitis score), blood glucose levels, and serum C‐peptide levels. Results:  Therapeutic administration of FTY720 to NOD mice with hyperglycemia (i.e. overt DM) significantly prolonged survival (P < 0.05 vs placebo). In the placebo group, all mice died within 63 days on the onset of DM; in contrast, 45% of FTY720‐treated mice survived during the observation period (up to 70 days after the onset of DM). Therapeutic administration of FTY720 in combination with insulin glargine to NOD mice with hyperglycemia further improved survival (P < 0.05) compared with either FTY720 or insulin glargine alone (i.e. 85% of FTY720 + insulin glargine‐treated mice survived to the end of the observation period). The efficacy of FTY720 in combination with insulin glargine was confirmed by histochemical, immunohistochemical and endocrinologic observations. Conclusions:  Combination therapy with FTY720 plus insulin glargine is a promising candidate for the treatment of DM and may allow for a reduction in the frequency of insulin self‐injections. (J Diabetes Invest, doi:10.1111/j.2040‐1124.2011.00160.x, 2011)